The Spectometric Quantification of Total Content of Flavonoid, Phenol, and Alkaloid in Kesum leaf (Polygonum minus Huds) from West Borneo with Methanol and Ethanol Solvent - Dian Kartikasari; Ika Ristia Rahman; Heni Puspasari; Abduh Ridha (Faculty of Pharmacy, Universitas Gadjah Mada, 2022)
Kesum (Polygonum minus Huds) is one of the typical plants that grow in West Borneo. The Kesum leaves are the part which is mostly used. Kesum leaves contain a lot of phytochemical compounds. This study quantitatively determined the total phenolic, flavonoid, and alkaloid contents in methanol and ethanolic extract of Polygonum minus Huds leaves using a spectrophotometric method. The samples were extracted by maceration. The content was determined by using a UV-Vis spectrophotometer. Based on the assay result, the methanol extract contained a total of phenolic 49.351±0.430 ppmEAG (equivalent to gallic acid); total of flavonoids 44.128±0.116ppmEQ (quercetin equivalent); total of alkaloids 356,798±1,004ppmEP (piperine equivalent). The 96% ethanol extract contained total of phenol 46,196±0.329ppmEAG; total of flavonoids 34,969±0.116ppmEQ; total of alkaloids 183.525±0.766ppmEP. The 70% ethanol extract contained total of phenol 64.189+0.215ppmEAG; total of flavonoids 27.834±0.158ppmEQ; total of alkaloids 432,947±1,533ppmEP. The ethanol extract 50% contained total of phenol 67,343±0.164ppmEAG; total of flavonoids 26.063±0.158ppmEQ; total of alkaloids 679,142±2,525ppmEP. All of the results are preliminary data for further research, especially for the isolation of compounds with specific targets or for utilization as main ingredients for traditional medicine.